Cultural intelligence and employee innovation performance in foreign trade companies: The role of innovative work behavior - Xin-Liufang, Xin-Liufang; Mohamad, Abang Azlan; Lo, May-Chiun (Edelweiss Applied Science and Technology, 2025)
As globalization intensifies, employees’ ability to navigate diverse cultural contexts becomes increasingly critical for fostering innovation in international trade. This study examines how cultural intelligence (CQ), which encompasses cognitive, metacognitive, motivational, and behavioral dimensions, enhances employee innovation performance (EIP) through innovative work behavior (IWB). Using data from 316 employees in Chinese foreign trade firms, structural equation modeling revealed that all CQ dimensions positively influence IWB, which fully mediates their impact on EIP. The study’s population includes Chinese foreign trade companies operating in six eastern provinces: Shandong, Jiangsu, Shanghai, Zhejiang, Fujian, and Guangdong. Partial least squares structural equation modeling (PLS-SEM) was selected for its robustness in handling complex models with small to moderate sample sizes, as well as its ability to prioritize prediction over theory testing (Hair et al., 2019). Participants, recruited from these six eastern Chinese provinces, were chosen due to their economic significance and cultural diversity. The quantitative analysis confirms significant relationships between CQ, IWB, and innovation outcomes, providing a robust framework for managers. By fostering cultural intelligence and innovative behaviors, organizations can effectively leverage their diverse workforce, establishing a sustainable competitive advantage in the global marketplace. These implications are especially relevant in foreign trade contexts, where adaptive and innovative approaches are essential for success. The findings underscore the necessity of fostering CQ to drive innovation in multicultural workplaces. The study advances the theoretical understanding of cross-cultural innovation dynamics and offers actionable strategies for managers in globalized industries.